2022
DOI: 10.3389/fphys.2021.791848
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis and Its Regulation in Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy (DbCM) is a prevalent disease, characterized by contractile dysfunction and left ventricular hypertrophy. Patients with DbCM have high morbidity and mortality worldwide. Recent studies have identified that pyroptosis, a kind of cell death, could be induced by hyperglycemia involved in the formation of DbCM. This review summarizes the regulatory mechanisms of pyroptosis in DbCM, including NOD-like receptor3, AIM2 inflammasome, long non-coding RNAs, microRNAs, circular RNA, autophagy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 128 publications
0
21
0
Order By: Relevance
“…The gray modules represent genes that had not been classified and, therefore, these were deleted. Because of the important effects of pyroptosis on diabetes ( Lu et al, 2021 ), we retrieved pyroptosis-related genes from the GeneCards database ( Stelzer et al, 2016 ), searching for the keyword criteria “pyroptosis”. Module analysis and mining were performed with the characteristics of pyroptosis-related genes to obtain modules significantly related to pyroptosis for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gray modules represent genes that had not been classified and, therefore, these were deleted. Because of the important effects of pyroptosis on diabetes ( Lu et al, 2021 ), we retrieved pyroptosis-related genes from the GeneCards database ( Stelzer et al, 2016 ), searching for the keyword criteria “pyroptosis”. Module analysis and mining were performed with the characteristics of pyroptosis-related genes to obtain modules significantly related to pyroptosis for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As pyroptosis and m5C have important effects on diabetes ( Liu et al, 2021 ; Lu et al, 2021 ), we determined if any genes of the pyroptosis module overlapped with m5C-related genes. A PPI network was constructed based on overlapping genes using the STRING database ( von Mering et al, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have shown that NLRP3 inflammasome activation can aggravate IR and lead to further damage to islet b cells and promote T2D progression (5,112,(116)(117)(118)(119); some recent studies have also demonstrated that the activation of the NLRP3 inflammasome mediates the pyroptosis of pancreatic b cells (108,120); for example, in the study of Yuan, J et al, the use of the NLRP3 inhibitor MCC950 ameliorated islet cell damage (121). Furthermore, pyroptosis mediated by the NLPR3 inflammasome plays a vital role in the progression of various complications such as diabetic nephropathy (DN) and diabetic cardiomyopathy (DCM) (Figure 3) (122)(123)(124)(125). Recent studies have shown the potential therapeutic role of the NLRP3 inflammasome/pyroptosis signaling pathway in type 2 diabetes and its complications.…”
Section: Nlrp3 Inflammasome-mediated Pyroptosis and Type 2 Diabetesmentioning
confidence: 99%
“…Cardiomyocytes maintain the systolic and diastolic functions of the heart and ensure the blood supply of the whole body ( 123 ). Under high glucose conditions, the NLRP3 inflammasome was activated through multiple pathways to induce pyroptosis in CMs.…”
Section: Macrovascular and Cardiac Complicationsmentioning
confidence: 99%
“…As a unique and programmed form of cell death, pyroptosis has been revealed to be associated with inflammatory response in DCM via releasing of pro-inflammatory intracellular contents including interleukin (IL)-1β, IL-18, and other inflammatory substances that are induced subsequent to the activation of the NLRP3 inflammasome which is linked to key cardiovascular risk factors ( 107 , 108 ). Meanwhile, emerging evidence has verified the role of non-coding RNAs in the pathogenesis of pyroptosis in DCM ( 109 ), including micro RNA (miRNA), circular RNA (circRNA), and long non-coding RNA (lncRNA) ( 110 ). Xu et al proved that suppression of NLRP3 inflammasome activation-mediated pyroptosis by targeted miR-34b-3p/AHR axis from long non-coding RNA GAS5 is valuable for the attenuation of DCM ( 111 ).…”
Section: Advance In Diabetic Cardiomyopathymentioning
confidence: 99%